A revised interview for deterioration in daily living activities in dementia reveals the relationship between social activities and well-being. (September 2016) - Giebel, Clarissa M; Challis, David J; Montaldi, Daniela
Background: The ability to perform instrumental activities of daily living deteriorates early in dementia and affects people with dementia and their carers. However, little is known about individual instrumental activities of daily living impairments. This study therefore investigated instrumental activities of daily living deficits in mild dementia by exploring the relationship between instrumental activities of daily living initiative and performance and general cognition, people with dementia quality of life and carer stress. Moreover, this study explored the contribution of social instrumental activities of daily livings, which to date have received little or no attention. Methods: Twenty carers were administered a revised Interview for Deterioration for Daily Living Activities in Dementia and measures of carer stress (General Health Questionnaire-12) and quality of life in dementia (Quality of Life in Alzheimer's Disease). The people with dementia completed measures of general cognition (Mini-Mental State Examination and Montreal Cognitive Assessment). Data were analysed using frequency and bivariate correlation analyses and basic thematic analysis was employed to the qualitative data on carer stress. Results: Carer interviews showed that instrumental activities of daily living impairments were associated more with performance than with initiative deficits. Increased social isolation and reluctance to engage in hobbies were particularly stressful to carers and impacted negatively on the people with dementia quality of life, yet were not reported as critical in the qualitative assessment. Conclusions: This study shows that people with mild dementia are impaired to different degrees on their initiative and performance of instrumental activities of daily livings and that impairments relating to social activities particularly relate to well-being. The revised Interview for Deterioration for Daily Living Activities in Dementia with its social instrumental activities of daily livings can help shift the focus of interventions to address those activities that are frequently impaired in mild dementia and relate to people with dementia and carer well-being.